Regeneration of Peasants - Zhao, Shukai (Springer Singapore : Imprint: Springer, 2017)
This book focuses on analyzing the inter-relationship between Chinese peasants and the reform and it tries to understand the conditions of peasants during the course of the Chinese social transition. This book argues that Chinese peasants are the most important force that keeps the reform going. More importantly, this book argues that this force comes from the peasants' pursuit of their own social, political and economic interest, not some spontaneous demand for "reform" itself. This inherent relationship between the peasants and the reform is summarized into five major relationships: the inter-relationship between peasants and the central government; between peasants and local government; between peasants and rural democratization; between peasants and social constructions; and between peasants and local officials. These five inter-relationships are the prime mechanism for the interaction between Chinese peasants and the reform, and these forms the basis for understanding and analyzing the inter-relationship between the state and peasants.
Keywords: Social sciences.; Political science.; Social policy.; Sociology.; elektronické knihy; electronic books